Effect of edible coating on the shelf life enhancement of apricot (Prunus armeniaca L.) - Wani, Sajad Mohd; Gull, Amir; Wani, Touseef Ahmad; Masoodi, Farooq Ahmad; Ganaie, Tariq Ahmad (Journal of Postharvest Technology, 2017)
The present study was carried out to extend the shelf life of fresh apricots by coating them with gum arabic and stored at refrigerated temperature for a period of 12 days. Coated apricots showed better physicochemical characteristics (moisture content, total soluble solids, titratable acidity) than the uncoated ones. Texture profile analysis of coated apricots showed better results than the uncoated ones. The antioxidant activity of coated apricots was also better preserved than uncoated ones. It is concluded here that edible coating of apricots with gum arabic and subsequent refrigerated storage could be employed for their better quality preservation.